Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1002/gps.930070505
|View full text |Cite
|
Sign up to set email alerts
|

Is there a desolation effect after dementia? A comparative study of mortality rates in spouses of dementia patients following admission and bereavement

Abstract: SUMMARYMortality rates following patient admission and patient death were measured in the surviving spouses of a sample of dementia patients admitted to a psychogeriatric unit between 1971 and 1986. The vital status of 85% of spouses was confirmed, and the ratio of observed to expected deaths (SMR) was calculated using regional and national mortality statistics.Spouse mortality following first admission to hospital was significantly lower than expected (p < 0.006), and spouse deaths following bereavement were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(39 reference statements)
2
5
0
Order By: Relevance
“…the ability of caregivers to prepare adequately for the predictable death of their spouse. (36) The theory of anticipatory grief is also consistent with our finding of similarly small (albeit statistically significant) widowhood effects in the wake of spouse’s death from cancers that typically lead to death quickly. This suggests that it may be the predictability of the death per se , rather than the duration of spouse’s terminal illness, that may shield the survivor from some of the adverse consequences of bereavement.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…the ability of caregivers to prepare adequately for the predictable death of their spouse. (36) The theory of anticipatory grief is also consistent with our finding of similarly small (albeit statistically significant) widowhood effects in the wake of spouse’s death from cancers that typically lead to death quickly. This suggests that it may be the predictability of the death per se , rather than the duration of spouse’s terminal illness, that may shield the survivor from some of the adverse consequences of bereavement.…”
Section: Discussionsupporting
confidence: 87%
“…Existing research often considers only a small number of causes of death, such as the broad categories of cancer or violent deaths,(15, 35-38) uses samples with relatively small numbers of cases for each individual cause of death, uses samples that are not nationally representative,(4, 35, 36, 39) uses a cross sectional methodology,(12, 14) or lacks statistical controls for confounding beyond age, sex, and race. (12, 14, 17, 37, 38) By contrast, this study considers 17 causes of death separately for both spouses in a longitudinal and nationally representative sample of 373,189 married couples experiencing a total of 317,300 deaths while adjusting for a wide range of covariates, including baseline health, that are measured for both members of the couple.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported by many subsequent workers (e.g. Magnusson, 1989;Black & Jolley, 1990;Burns et al, 1990;Ryan, 1993). Puxty et al (1983) had found bronchopneumonia to be the most common immediate cause of death among older people dying after admission to acute medical wards.…”
Section: Dementia Spectrum Diagnosissupporting
confidence: 86%
“…Barclay et al, 1985W. Family history Knesevich et al (1985) found that cases with a family history of dementia lived longer than those without such a history. Ryan (1992) found that patients suffering from dementia died before their (non-demented) spouses, but marital status did not influence survival among patients referred to Salford psychiatric services (Jolley, 1996). Magnusson (1989) found longer survival in social class I.…”
Section: Agementioning
confidence: 99%
“…Low vitamin C intake appears to increase both the risk of developing cognitive impairment and subsequent mortality (Gale et al, 1996). Ryan (1992) found that survival among patients suering from dementia was less than their spouses; but that the impact of either partner's death had no eect on the other's duration of survival. Aphasia (Faber-Langendoen et al, 1988), parietal lobe dysfunction (McDonald, 1969;Burns et al, 1991), psychotic features (Stern et al, 1987) and behavioural abnormalities at the time of presentation or assessment (Barclay et al, 1985;Diesfeldt et al, 1986;Moran et al, 1990) are all associated with shorter survival times (Stern et al, 1987).…”
mentioning
confidence: 98%